Engineering Properties of Marine Soils and Offshore Foundations - Youkou Dong; Dengfeng Fu; Xiaowei Feng (Journal of Marine Science and Engineering)
To reduce greenhouse gas emissions and enhance energy security, the role of renewable energy in the global energy structure is becoming increasingly significant [...]